Epibiotic bacterial community composition varies during different developmental stages of Octopus mimus: Study of cultivable representatives and their secondary metabolite production. - Martha B Hengst; Stephanie Trench; Valezka Alcayaga; Cristian Sepúlveda-Muñoz; Jorge Bórquez; Mario Simirgiotis; Fernando Valenzuela; Mario Lody; Lenka Kurte; Coral Pardo-Esté (PLoS ONE)
Marine microbial communities colonizing the skin of invertebrates constitute the primary barrier between host and environment, potentially exerting beneficial, neutral, or detrimental effects on host fitness. To evaluate the potential contribution of epibiotic bacteria to the survival of early developmental stages of Octopus mimus, bacterial isolates were obtained from eggs, paralarvae, and adults. Their enzymatic activities were determined, and antibacterial properties were assessed against common marine pathogens. The isolates belonged to the phyla Proteobacteria, Actinomycetota, Bacteroidota, and Bacillota, represented by 21 genera and 27 species. Specific taxa were associated with each developmental stage, with only three species shared among different stages: Bacillus pumilus, B. megaterium, and Shewanella algae, which also inhibited the growth of all assayed pathogens. Organic extracts from Bacillus megaterium M8-1 were obtained, and UHPLC-MS analysis detected seventeen putative compounds, including two phenolic acids, three indole derivatives, and twelve oxylipins. Our findings provide novel data on cultivable bacterial representatives isolated from Octopus mimus capable of synthesizing chemical compounds with bioactive properties. These results contribute to a better understanding of the role of microbial communities in the survival of this invertebrate species during critical early life stages.